Penentuan Status Gizi Pada Balita Menggunakan Fuzzy Inference System Dengan Metode Fuzzy Tsukamoto - Vandelweiss, Dita Aura; Fauzi, Ahmad; Kusumaningrum, Dwi Sulistya; Baihaqi, Kiki Ahmad (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Nourishing status in babies is a vital consideration of guaranteeing sound development and improvement. This exploration plans to foster a specialist framework for nourishing status in babies using the fluffy surmising framework strategy with the Tsukamoto fluffy calculation in view of body weight and level. In light of essential information overviews and meetings, the information gathered from coordinated wellbeing, in particular Posyandu West Adiarsa, Adiarsa Pusaka, and Telukjambe Timur in Karawang Regime added up to 181 information on kids under five. Framework configuration incorporates a point of interaction framework consisting of information, yield, data set, information construction and calculation framework plan. Framework execution was done using HTML, PHP, MySQL, and Cup. The testing framework includes a fluffy deduction framework using the Tsukamoto fluffy technique on various review instances of young children with different dietary circumstances, with contribution of 3 factors consisting; old enough, weight, level. The experimental outcomes will be contrasted and the nourishing is not entirely set in stone by a nutritionist. This exploration produces fluffy sets for the factors of weight, level and healthful status, as well as fluffy registering decisions that interface information and results. The test brings about the framework obtained a precision of 96% on the grounds that 181 tests were carried out on each information variable which adapted the factors 'terrible', 'less', 'typical', 'more' and 'weight'.